Tantangan Dakwah Dalam Arus Perkembangan Media Sosial - Tomi Hendra; Siti Saputri (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The development of social media today seems like mushrooms that blossom in the rainy season. Where the presence of social media has removed the veil that is in the midst of social life. Likewise in the world of da’wah, social media gives a new color in its development, so that in practice the dak’wah has shifted, currently preaching is not only from the pulpit pulpit but by sitting sweetly in front of a television screen or computer mad’u has been able to enjoy propaganda. In its development, social media currently generally supports and becomes an unparalled propanganda media. This can be seen from the number of da’wah interpreters who use social media for da’wah, such as; youtube, instagram, facebook and the like. The advancement and up-to-date social media not only gives positive inpact and response to the world of da’wah, like two sides of a coin, there is a positive side that is felt by the da’wah world. The other side also presents a new challenge for the world of dak’wah. One of the cases that can be explainde, often mad’u can not confirm or ask directly related to mataerial that is not understood, so mad’u must swallow raw material preaching delivered by the preacher. The next problem is that a da’wah interpreter cannot see the extent to which the da’wah material delivered changes to mad’u and the extent to which da’wah delivered through social media brings change to mad’u this is among the da’wah challenges that must be faced by interpreters in the current development of social media. In this case the researcher tried to explain the challenges of da’wah in the flow of the development of social media by using the qualitative descriptive method.